Research Related Tumour Biopsies in Early-Phase Trials with Simultaneous Molecular Characterisation – a Single Unit Experience. (2021) - Biondo, Andrea; Pal, Abhijit; Riisnaes, Ruth; Shinde, Rajiv; Tiu, Crescens; Lockie, Fran; Baker, Chloe; Bertan, Claudia; Crespo, Mateus; Ferreira, Ana; Pereira, Rita; Figueiredo, Ines; et al.
Highlights: The pharmacological audit trail is still fundamental to cost effective drug development and while liquid biopsies are emerging, tissue biopsies remain the gold standard for establishing pharmacodynamic data, proof of concept and proof of mechanism Research related biopsies have been ethically controversial for questions around potential harm at the end of life without any concomitant benefit to the patient We demonstrate, in our large single operator US-guided research biopsy case series, that research related biopsies can be safe and with a low complication rate In addition, we show that a parallel sequencing program can yield valuable molecular information ABSTRACT: Early-phase cancer clinical trials are becoming increasingly accessible for patients with advanced cancer who have exhausted standard treatment options and later phase trial options. Many of these trials mandate research tissue biopsies. Research biopsies have been perceived as ethically fraught due to the perception of potential coercion of vulnerable human subjects. We performed an audit of two years of practice to assess the safety of ultrasound (US)-guided research biopsies, and to look at the yield of a simultaneous tumour next-generation sequencing (NGS) and immunohistochemistry (IHC) molecular characterisation programme. We show that in our institution, US-guided research biopsies were safe, produced adequate tumour content and in a selected subset who underwent in-house NGS sequencing, showed a high rate of actionable mutations with 30% having a Tier 1 variant. Nevertheless, these research biopsies may only provide direct benefit for a minority of patients and we conclude with a reflection on the importance of obtaining truly informed consent.